Five new species of Coeliccia Kirby, 1890 from Vietnam (Odonata: Platycnemididae), and information on several other species of the genus - Kompier, Tom; Dow, Rory A.; Steinhoff, Philip O.m. (Zootaxa, 2020)
Five new species of Coeliccia (Coeliccia caerulea sp. nov. [holotype: Bao Loc, Lam Dong Prov., appr. 11.449N, 107.712E], Coeliccia coronata sp. nov. [holotype: Bao Loc, Lam Dong Prov., appr. 11.726N, 107.713E], Coeliccia curua sp. nov. [holotype: Ba Be National Park, Bac Kan Prov. appr. 22.413N, 105.610E], Coeliccia diomedea sp. nov. [holotype: Tai Giang, Quang Nam Prov., appr. 16.006N, 107.507E], and Coeliccia pulchella sp. nov. [holotype: Huu Lien Nature Reserve, Lang Son Prov., appr. 21.662N, 106.373E]) are described from Vietnam. The females of C. galbina Wilson & Reels, 2003, C. hayashii Phan & Kompier, 2016 and C. suoitia Dow, 2016 are described. Coeliccia montana Fraser, 1933 is shown to be a junior synonym of C. pyriformis Laidlaw, 1932.